2009
DOI: 10.7205/milmed-d-05-0308
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Test Interpretation Using Age-Matched Controls to Evaluate Exertional Dyspnea

Abstract: The use of age-matched controls for CPET results in an increase in specificity and decrease in sensitivity for respiratory limitations to exercise, when compared to reference values. The study findings suggest that CPET may be insensitive in detecting mild disease in young healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…A recent study by Sill et al examining CPET in a similar normal population of military personnel (mean age of 25.4 ± 4.3 years, body mass index of 24.4 ± 2.8, and percent body fat of 21.3 ± 6.1) found only a slight decrease in the predicted normal VO 2 max to 82% predicted [7]. In a 1974 study in which 710 healthy, active duty Air Force personnel underwent maximal exercise testing, the authors published a regression equation used to predict VO 2 max.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Sill et al examining CPET in a similar normal population of military personnel (mean age of 25.4 ± 4.3 years, body mass index of 24.4 ± 2.8, and percent body fat of 21.3 ± 6.1) found only a slight decrease in the predicted normal VO 2 max to 82% predicted [7]. In a 1974 study in which 710 healthy, active duty Air Force personnel underwent maximal exercise testing, the authors published a regression equation used to predict VO 2 max.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Sill et al . [ 9 ] compared the CPET findings in 105 patients with exercise-induced dyspnea with 69 normal volunteers and observed that the use of CPET in patients with exercise-induced dyspnea causes the increased specificity and the reduced diagnosis sensitivity. They stated that the CPET has not the required sensitivity in diagnosis of mild illness in young people.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the younger military population, there is little cardiac disease and the presence of most pulmonary disease can be detected by other testing. Additionally, there are no established reference values for CPET parameters in this population [Sill et al 2009]. Despite these limitations, CPET may provide an estimate of the patient’s ability to perform maximal exercise, which is important in determining further invasive testing.…”
Section: Evaluation Of Deployed Military Personnelmentioning
confidence: 99%